Impact of prenatal and environmental factors on child growth: Evidence from Indonesia - Yamauchi, Futoshi; Higuchi, Katsuhiko; Suhaeti, Rita Nur (Japan International Cooperation Agency, 2010)
This paper examines the impacts of prenatal conditions and water quality on child growth using recent data from Indonesia. Our empirical results show that an increase in birthweight has significant positive effects on children's subsequent height and weight-for-age z scores, whereas an improvement in drinking water quality, as measured by coliform bacteria count, increases the weight-for-height z score. Interestingly, there is seasonality in birthweight; this measure is significantly higher during the dry season than during the rainy season, and is also higher in a Christian-majority province than in Muslim-majority provinces, during the period shortly after Ramadan. Finally, the availability of modern water infrastructure improves the quality of drinking water. These findings show that interactions of environmental variations affect early childhood human capital formation and can have long-term impacts on their outcomes.